The English North-South divide: risk factors for cardiovascular disease accounting for cross-sectional socio-economic position. - Kumar, R; Dalton, A (SAGE Publications, 2014)
AIMS: Given a North-South divide in mortality in England, we aimed to assess the extent of a North-South divide in risk factors for cardiovascular disease (CVD), controlling for markers of socio-economic position (SEP). METHODS: We undertook cross-sectional analyses using respondents from the 2006 Health Survey for England. We assessed mean systolic blood pressure, total cholesterol, body mass index (BMI) and smoking prevalence in the two regions. We built nested regression models adding demographic factors, SEP indicators, behavioural risk factors, vascular disease status and CVD preventive medications stepwise into each model. We examined interactions between region, age and gender. RESULTS: Controlling for demographic variables, we found a northern excess in systolic blood pressure (+1.95mmHg (SE = 0.40)), BMI (0.40kgm(-2) (SE = 0.12)) and smoking prevalence (5.6% (SE = 1.1)). The difference in smoking prevalence was entirely abolished by markers of SEP. Systolic blood pressure and BMI differences were attenuated by SEP, behavioural and disease indicators, but remained (+1.63mmHg (SE = 0.41) and 0.25kgm(-2) (SE = 0.12), respectively). However, they were lost after adjustment for preventive medication. The North-South divide in systolic blood pressure was attributed to differences in men and younger-to-middle-aged groups. Northern respondents were more physically active, especially younger men. CONCLUSIONS: English North-South differences in smoking can be explained through adverse, cross-sectional SEP. Northern excesses in blood pressure and BMI may be associated with differential clinical management. Risk factor differences may, in part, explain a previously found North-South divide in mortality. Further exploration of geographic inequalities, concentrating on the impact of healthcare, may be warranted.